ICASSP '85. IEEE International Conference on Acoustics, Speech, and Signal Processing
DOI: 10.1109/icassp.1985.1168525
|View full text |Cite
|
Sign up to set email alerts
|

Adaptive noise reduction in aircraft communication systems

Abstract: It has been reported that the application of broadband noise cancelling techniques to the control of aircraft cockpit noise pickup is only successful at low frequencies. This effect is explained in terms of measures of the noise transmission across a standard British oxygen mask and a discussion of the spatial characteristics of the cockpit's acoustic field. A theoretical prediction of the maximum noise reduction given by a single channel noise cancelling system controlling a group of independantly excited noi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 2 publications
0
3
0
Order By: Relevance
“…The LMS algorithm, developed by Hoff in 1959 ͑Widrow et al, 1985;Haykin et al, 1986͒, has been studied in great detail and has found a myriad of applications ͑Widrow et al, 1975;Darlington et al, 1985;Rodriguez et al, 1987;Harrison et al, 1986;Pulsipher et al, 1979;Elliott et al, 1987;Poole et al, 1984͒. Figure 2͑a͒ depicts the basic construct for noise reduction in a linear system with additive noise.…”
Section: A Least-mean-squares "Lms… Algorithmmentioning
confidence: 98%
“…The LMS algorithm, developed by Hoff in 1959 ͑Widrow et al, 1985;Haykin et al, 1986͒, has been studied in great detail and has found a myriad of applications ͑Widrow et al, 1975;Darlington et al, 1985;Rodriguez et al, 1987;Harrison et al, 1986;Pulsipher et al, 1979;Elliott et al, 1987;Poole et al, 1984͒. Figure 2͑a͒ depicts the basic construct for noise reduction in a linear system with additive noise.…”
Section: A Least-mean-squares "Lms… Algorithmmentioning
confidence: 98%
“…The correlation between the noise present in the reference channel and the primary input is important: the higher it is, the better the cancellation [13]. A diagram of the concept is pictured in Fig.…”
Section: Theorymentioning
confidence: 99%
“…This was circumvented by adapting the filter used for cancellation only during periods of background noise. A more realistic evaluation [13] of the cockpit environment was performed by simulating a diffuse background noise field and it was concluded that good cancellation was not possible at frequencies above 2 kHz. The study identified coherence between the reference and primary channels as the most important factor in successful cancellation.…”
Section: Introductionmentioning
confidence: 99%